Acupuncture for Psychological Disorders Caused by Chronic Pain: A Review and Future Directions - Lin, Lu-Lu; Li, Hong-Ping; Yang, Jing-Wen; Hao, Xiao-Wan; Yan, Shi-Yan; Wang, Li-Qiong; Yu, Fang-Ting; Shi, Guang-Xia; Liu, Cun-Zhi (Frontiers in Neuroscience, 2021)
Accumulating evidence supports an association between chronic pain and psychological disorders, a connection that seems to be bidirectional. Treating both the pain and psychological conditions together is essential for effective treatment outcomes. Acupuncture as a somatosensory-guided mind-body therapy that can tackle the multidimensional nature of pain with fewer or no serious adverse effects. In this review, we discuss the use of acupuncture in some conditions with a high incidence of psychological disorders caused by chronic pain: headache, musculoskeletal pain, low back pain and cancer pain, focusing on the effect and potential mechanisms of acupuncture. Overall clinical studies indicated that acupuncture might effectively contribute to management of psychological disorders caused by chronic pain. Mechanistic studies showed that acupuncture significantly alleviated such psychological disorders by regulating the activity of amygdala and insula, and regulating functional connectivity of insular and limbic regions/medial prefrontal cortex in human and the corresponding animal models. In addition, 5-HT in the dorsal raphe nucleus, opioid receptors in the cingulate cortex and plasma met-enkephalin are involved in acupuncture relief of pain and psychological symptoms. Substantial evidences from animal and human research support a beneficial effect of acupuncture in psychological disorders caused by chronic pain.